Implementasi Program Labbaik dalam meningkatkan Mutu Pembelajaran Kitab Kuning Santri - Robi’atul Adhawiyah (Rihlah Review: Jurnal Pendidikan Islam, 2022)
The LABBAIK Program (Institute for Quran and Book Reading Guidance) at PP Mambaus Sholihin Suci Gresik is a mandatory program for students enrolled at MA Mambaus Sholihin and UNKAFA university students. This program consists of two activities: the first focuses on guiding fluency in reading the Quran, and the second involves studying the book "Fathul Qorib Al-Mujib," guided by the institution's administrators and ustadz (religious teachers) from the Islamic boarding school. However, this research specifically concentrates on the guidance activities related to the yellow book. The objective of this research is to determine whether the LABBAIK program has been implemented as planned and to assess the improvements that occur after high-quality learning is carried out. This is aimed at producing students who are capable of reading, interpreting, and explaining the contents of the book. The research employed a descriptive qualitative approach, utilizing primary data from interviews with three instructors and observations at the Islamic boarding school. Secondary data comprised learning documentation, which served as a data collection technique. Upon conducting data analysis through data reduction, data presentation, and data verification, this study's results demonstrated the program's successful implementation as planned. The majority of students were not only able to read the book fluently but also to translate its content and to elucidate its meaning within each section of the book. Additionally, their ability to explain the book's content in terms of the grammatical and linguistic aspects (nahwu shorof) had shown considerable improvement, as evidenced by the minimal number of students requiring repetition during the "sorogan" sessions. Therefore, to assess student quality, a LABBAIK program exam was conducted prior to graduation, directly overseen by senior faculty members and Islamic boarding school mentors